Meditate with Me : A Step-by-step Mindfulness Journey - Gates, Mariam; Surnaite, Margarita (New York, NY Dial Books for Young Readers, 2017)
"A classroom full of animals demonstrates the principles of mindfulness in this guide to meditation for children"--
Keywords: Meditation -- Juvenile literature; Mindfulness (Psychology) -- Juvenile literature; Meditation; Mindfulness (Psychology)